Letter from Ruth Ehrlich - Ruth Ehrlich:::::: (1968)
In a letter to convention delegates, Ruth Ehrlich urges recognition of women's rights as a major civil rights issue, arguing that women—though 51% of the population—continue to face discrimination in employment, pay, and political participation. She calls on the Democratic Party to add a Women's Rights section to its platform, building on a program already adopted by the California Democratic Council and supported by organizations such as NOW. The letter includes a call to action, asking delegates to endorse the program, participate in convention efforts, contribute funds, and support ongoing advocacy to secure greater equality and representation for women in public life.